2019
DOI: 10.1021/acsomega.8b03629
|View full text |Cite
|
Sign up to set email alerts
|

Stability Improvement of Perovskite Solar Cells for Application of CuInS2 Quantum Dot-Modified TiO2 Nanoarrays

Abstract: In this work, we developed a CH 3 NH 3 PbI 3 perovskite solar cell with CuInS 2 quantum dot-modified TiO 2 nanoarrays (TiO 2 –CuInS 2 QD-NAs) as a scaffold layer. Based on the suitable device configuration, we achieved improved power conversion efficiency (PCE) of 13.3%, which was 38.3% higher than that of the device without QD modification (8.2%). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…[ 6 ] For example, ZnO has been found to deprotonate the organic phase of perovskite [ 7 ] and TiO 2 can also decompose perovskite into MA and PbI 2 due to its high ultraviolet activity, [ 8 ] which are the mortal threats to the reliability of PSC applications. [ 9 ] TiO 2 and SnO 2 , the most promising ETMs in planar PSCs, are not always ideal for efficient charge extraction due to their low electron mobility, large energy barrier, and vast uncoordinated defect sites. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] For example, ZnO has been found to deprotonate the organic phase of perovskite [ 7 ] and TiO 2 can also decompose perovskite into MA and PbI 2 due to its high ultraviolet activity, [ 8 ] which are the mortal threats to the reliability of PSC applications. [ 9 ] TiO 2 and SnO 2 , the most promising ETMs in planar PSCs, are not always ideal for efficient charge extraction due to their low electron mobility, large energy barrier, and vast uncoordinated defect sites. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, a lower R s indicates a higher FF. To conform the J sc as well as the FF, we got deep investigations in the resistance of the series by the typical equation (eq ), where I L and I 0 represent the photocurrent ( n = 1) and dark saturation current (reverse polarization), respectively. q , T , K , and V are the values of the charging, absolute temperature, Boltzmann constant, and bias potential, respectively. …”
Section: Resultsmentioning
confidence: 99%
“…The band gap of CuInS 2 QDs is approximately 1.6 eV, which effectively optimized the energy level alignment between the two layers and facilitated charge transport, resulting in a PCE of 11.70% for the final device based on CuInS 2 QDs as the interface. In the following time, they prepared CuInS 2 QDs in the size range of 1 nm to 3 nm in 2019 [97], which were again used as an interface between TiO 2 nanorods and perovskite. XRD showed that CuInS 2 QDs strongly influence the crystallization of perovskite, promoting the growth of CH 3 NH 3 PbI 3 crystals along the (312) crystal plane.…”
Section: Gqd-modified Perovskite/etl Interfacementioning
confidence: 99%